Teachers’ Professional Journeys: Life Histories of Female Educators in Northern Nigeria - Emeka Nwosu; Bola Oladeji; Ifeoma Okechukwu (Yayasan Adra Karima Hubbi, 2025)
Background. In Northern Nigeria, female educators face a unique intersection of cultural, religious, and structural challenges that shape their access to and progression within the teaching profession. Despite policy efforts to increase female participation in education, little is known about the personal and professional experiences of women who navigate these constraints to become educators. Purpose. This study explores the life histories of female teachers in Northern Nigeria to understand how they construct their professional identities and sustain their careers within a socio-cultural landscape marked by gender expectations, limited mobility, and resource scarcity. Method. Using a qualitative life history approach, the study involved narrative interviews with 15 female teachers across rural and peri-urban settings in Kano, Katsina, and Kaduna states. Results. Thematic analysis revealed key patterns related to family influence, resilience in the face of structural adversity, mentorship, and the moral dimensions of teaching as social service. Participants shared stories of early inspiration, periods of withdrawal due to marriage or childbirth, and eventual returns to teaching motivated by a sense of community duty. Conclusion. The study concludes that life history narratives provide critical insight into the agency, adaptation, and persistence of women educators in marginalized regions.